2022
DOI: 10.1007/s11356-022-24618-w
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cesium and strontium for radioactive wastewater by Prussian blue nanorods

Abstract: In this work, novel Prussian blue tetragonal nanorods were prepared by template-free solvothermal methods for removal of radionuclide Cs and Sr. It was worth that Prussian blue nanorods exhibited the better adsorption performance than co-precipitation PB or Prussian blue analogue composites. Thermodynamic analysis implied that adsorption process was spontaneous and endothermic which was described well with Langmuir isotherm and pseudo-second-order equation, the maximum adsorption capacity of PB nanorod was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Table 5 showed that without any reagent addition, the pyrite surface was negatively charged with a value of −10.37 mV at pH 9, which reflected the surface oxidation and the formation of ferric hydroxide at alkaline pH values. Upon Fe(CN) 6 3− addition, the potential value was dramatically shifted to a more negative −37.36mV, demonstrating the chemical adsorption of Fe(CN) 6 3− on iron sites of pyrite and the resulted formation of Prussian Blue, the zeta potential of which has been reported around −37.5~−33 mV [39][40][41][42]. Upon the addition of lead ions, the potential value significantly increased to 31.02 mV; this means that lead species chemically adsorbed on the pyrite surface.…”
Section: Zeta Potential Of Pyrite Surfaces Upon Addition Of Lead Ions...mentioning
confidence: 99%
“…Table 5 showed that without any reagent addition, the pyrite surface was negatively charged with a value of −10.37 mV at pH 9, which reflected the surface oxidation and the formation of ferric hydroxide at alkaline pH values. Upon Fe(CN) 6 3− addition, the potential value was dramatically shifted to a more negative −37.36mV, demonstrating the chemical adsorption of Fe(CN) 6 3− on iron sites of pyrite and the resulted formation of Prussian Blue, the zeta potential of which has been reported around −37.5~−33 mV [39][40][41][42]. Upon the addition of lead ions, the potential value significantly increased to 31.02 mV; this means that lead species chemically adsorbed on the pyrite surface.…”
Section: Zeta Potential Of Pyrite Surfaces Upon Addition Of Lead Ions...mentioning
confidence: 99%
“…Developing new or conducting existing treatment methodologies is considered an essential step in nuclear waste safety (Yao et al 2022 ). Environmental contamination produced by the periodic discharge of effluents from industrial waste into geo and biospheres has become a global catastrophe, especially in this century.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al, ( 2022 ) used a flocculation method based on an inorganic washing solution to remove Cs + and Sr 2+ from the soil, while co-precipitation was used by Sopapan et al, ( 2023 ) via the application of potassium ferrocyanide to remove 134,137 Cs from low and intermediate level liquid radioactive waste. Also, another advanced technology such as membrane separation, ion exchange, and adsorption has been carried out for the removal of cesium and strontium radionuclides (El-Nagaar et al 2012 ; El-Aryan et al 2014 ; Rizk and Hamed 2015 ; Li et al 2017 ; Nasseh et al 2017 ; Abdel-Galil et al 2018 , 2020 , 2021 ; Mahrous et al 2019 , 2022a , c ; Amesh et al 2020 ; Pham et al 2020 ; Akinhanmi et al 2020 ; Bediako et al 2020 ; Cheng et al 2020 ; Yang et al 2021 ; Abass et al 2022 ; Lee et al 2022 ; Patra et al 2022 ; Yao et al 2022 ; Șenilă et al 2023 ; Sopapan et al 2023 ) using organic, inorganic, or composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, work to evaluate the impact of co-existing ions on the effectiveness of the Tube-D-PB shuttles to remove Cs ions from simulant and actual waste streams is called for; although precedent exists to suggest that grafted PB would retain good selectivity for Cs ions vs. common co-existing ions that might be expected in accident and emergency scenarios such as Na, Mg, Sr, Co and U. 15,16 Yet, successful unimpeded recovery is not a foregone conclusion considering ion radii and charge density of certain cations being similar enough to Cs to suppress selective recovery, notably K. 15,17 Analysis of other parameters e.g. pH is also needed.…”
mentioning
confidence: 99%